Addressing the Effect of Exercise on Glial Cells: Focus on Ependymal Cells - Grazia Maugeri; Alessandra Amato; Giuseppe Evola; Velia D’Agata; Giuseppe Musumeci (Journal of Integrative Neuroscience)
A growing body of research highlights the positive impact of regular physical activity on improving physical and mental health. On the other hand, physical inactivity is one of the leading risk factors for noncommunicable diseases and death worldwide. Exercise profoundly impacts various body districts, including the central nervous system. Here, overwhelming evidence exists that physical exercise affects neurons and glial cells, by promoting their interaction. Physical exercise directly acts on ependymal cells by promoting their proliferation and activation, maintaing brain homeostasis in healthy animals and promote locomotor recovery after spinal cord injury. This review aims to describe the main anatomical characteristics and functions of ependymal cells and provide an overview of the effects of different types of physical exercise on glial cells, focusing on the ependymal cells.